2017
DOI: 10.1159/000469662
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predictors of ≥5% Weight Loss by Multidisciplinary Advice to Severely Obese Subjects

Abstract: Background:Weight loss success is determined by genetic factors, which may differ according to treatment strategy. Methods: From a multidisciplinary obesity treatment program involving dietary advice, psychological counseling, and increased physical activity, 587 subjects (68% female; 46.1 ± 12.4 years; BMI 39.9 ± 6.3) were recruited. At baseline, a blood sample was drawn for DNA isolation. Genotypes were determined for 30 polymorphisms in 25 candidate genes. The association between genotypes and weight loss w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Among the most remarkable findings of the present study, we have the greater reduction in absolute fat mass shown by the carriers of the TT genotype of the rs1052700 variant of the PLIN1 gene compared to the AA and AT genotypes (Table 5). These results are concordant with that found by Aller et al (2017), where they reported an association between the TT genotype of the PLIN1 rs1052700 polymorphism and the reduction of body mass ≥5% following 3 months of a multidisciplinary intervention with dietary advice, psychological counseling, and increased physical activity in a Caucasian obese population (Aller et al, 2017). In addition, a haplotype of two SNPs of the PLIN1 gene, 13041A>G (rs2304795) and 14995A>T (rs1052700), has previously been associated with obesity risk (Qi et al, 2004) and with response to a 6-month endurance exercise intervention (Jenkins et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Among the most remarkable findings of the present study, we have the greater reduction in absolute fat mass shown by the carriers of the TT genotype of the rs1052700 variant of the PLIN1 gene compared to the AA and AT genotypes (Table 5). These results are concordant with that found by Aller et al (2017), where they reported an association between the TT genotype of the PLIN1 rs1052700 polymorphism and the reduction of body mass ≥5% following 3 months of a multidisciplinary intervention with dietary advice, psychological counseling, and increased physical activity in a Caucasian obese population (Aller et al, 2017). In addition, a haplotype of two SNPs of the PLIN1 gene, 13041A>G (rs2304795) and 14995A>T (rs1052700), has previously been associated with obesity risk (Qi et al, 2004) and with response to a 6-month endurance exercise intervention (Jenkins et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…53 Aller and colleagues found that polymorphisms in genes related to the regulation of fat storage and adipocyte structure adaptation predicted 3- and 12-month weight loss to an LMT program. 52 Samblas and colleagues showed that, among adults undergoing a 6-month dietary modification program, baseline CD44 in white blood cells showed lower expression and higher DNA methylation levels in those who achieved 8% or greater weight loss compared with those achieving less than 8%. 60 This suggests that CD44 gene transcription and methylation may be a useful biomarker for weight loss prediction.…”
Section: Heterogeneity In the Effectiveness Of Interventions For The mentioning
confidence: 99%
“…In the present study, no significant association between BDNF , TMEM18 , and SEC16B and changes in anthropometric traits after 12 months could be shown. Existing literature on the same SNPs or SNPs in high LD to those analysed in this study showed no significant association with weight loss after 6 or 12 months in adults with overweight and obesity: rs6548238 of the TMEM18 gene, rs6265 of the BDNF gene, rs10913469, and rs543874 of the SEC16B gene [ 6 , 30 ]. However, the analysis of weight loss rate (kg/year/allele) showed a significant association of the C risk allele in the BDNF SNP rs6265 with a higher weight loss rate [ 30 ].…”
Section: Discussionmentioning
confidence: 61%
“…To test this hypothesis obesity-related single nucleotide polymorphisms (SNPs) have been investigated for associations with weight loss during lifestyle interventions. The role of SNPs in obesity therapy has been shown in some studies for genes like peroxisome proliferator-activated receptor gamma ( PPARG ) [ 5 , 6 ], matrix metalloproteinase 2 ( MMP2 ), Perilipin-1 ( PLIN1 ), and metalloproteinase inhibitor 4 ( TIMP4 ) [ 6 ], while others did not show evidence for an association between SNPs and weight loss [ 7 , 8 , 9 ]. A systematic review and meta-analysis on the effect of the fat mass and obesity-associated ( FTO ) gene on weight loss demonstrated that the response to weight loss intervention was not significantly different between FTO genotypes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%